2012
DOI: 10.1029/2012ja018163
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characteristics of equatorial plasma bubbles detected by the C/NOFS satellite near the sunset terminator

Abstract: We present the observations of equatorial plasma bubbles in the evening sector by the Communication/Navigation Outage Forecasting System (C/NOFS) satellite during 2011. We illustrate with a few examples the overall properties of the equatorial ionosphere as the solar activity approached maximum. C/NOFS was often below the F peak and this allowed us to examine the early phases of irregularity formation. We show examples when C/NOFS detected a continuous generation of plasma bubbles near the sunset terminator ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 33 publications
8
65
0
Order By: Relevance
“…The observed EPBs had maximum zonal widths of 100–500 km and propagated distance of 440–3000 km toward the east with velocities of 83 to 162 m s −1 , which are consistent with those in previous studies [ Kelley , ; Chapagain et al , ; Makela and Otsuka , ]. The lifetime of each striation was in the range from 50 min to 7 h. The lifetimes of EPBs for several hours are consistent with the (C/NOFS) observation by Huang et al [] who observed lifetimes of 3 and 7 h during high and low solar activities, respectively. The shortest lifetime of an EPB obtained from the ROTI keogram of 50 min was characterized by a small zonal width and low ROTI value.…”
Section: Discussionsupporting
confidence: 91%
“…The observed EPBs had maximum zonal widths of 100–500 km and propagated distance of 440–3000 km toward the east with velocities of 83 to 162 m s −1 , which are consistent with those in previous studies [ Kelley , ; Chapagain et al , ; Makela and Otsuka , ]. The lifetime of each striation was in the range from 50 min to 7 h. The lifetimes of EPBs for several hours are consistent with the (C/NOFS) observation by Huang et al [] who observed lifetimes of 3 and 7 h during high and low solar activities, respectively. The shortest lifetime of an EPB obtained from the ROTI keogram of 50 min was characterized by a small zonal width and low ROTI value.…”
Section: Discussionsupporting
confidence: 91%
“…Huang et al . [] recently reported the generation of equatorial plasma bubbles in the evening sector observed by the Communication/Navigation Outage Forecasting System (C/NOFS) satellite. They found that plasma bubbles can be continuously generated near the sunset terminator for 12 h over the longitudinal range of Asia, Africa, and the Atlantic region.…”
Section: Introductionsupporting
confidence: 84%
“…Observational evidence of large-scale wave structure and its possible role in the generation of ESF irregularities was reported by Tsunoda and White (1981) and Thampi et al (2009). Although ESF irregularities and plasma bubbles appear to be periodic sometimes (e.g., Huang et al 2013), they are irregular and not periodic in most cases (e.g., Huang et al 2012). Choi et al (2017) analyzed C/NOFS data and found that a representative periodicity does not exist in the occurrence of bubbles and that the bubble spacing is generally irregular.…”
Section: Definition Of Esf Irregularitiesmentioning
confidence: 99%
“…If only a small number of events are used, it is likely to find that ESF occurs when the PRE is larger than some values. For example, Huang et al [2012] analyzed C/NOFS data in 2 days and found that plasma bubbles were generated during 15 orbits when the PRE peak V i was 40-70 m/s. If we only examined these 15 events, the conclusion would be that plasma bubbles occurred when the PRE peak V i was larger than 40 m/s.…”
Section: Connection Among the Three Relationships Between The Pre Andmentioning
confidence: 99%